2019
DOI: 10.1002/mar.21312
|View full text |Cite
|
Sign up to set email alerts
|

Brand engagement in self‐concept and consumer engagement in social media: The role of the source

Abstract: This three-group between-subjects experimental research investigates the extent to which consumer engagement with a social media branded post is directly affected by individuals' tendency to incorporate brands as part of their self-concept (BESC) and whether this relationship is moderated by individuals' exposure to three different post source types. Participants were exposed to one of three Instagram social media posts of a luxury brand, where the only manipulated factor was the type of source.Findings show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 57 publications
1
84
0
3
Order By: Relevance
“…Regarding the use of social media in the business context, several works can be highlighted [15][16][17][18][19]. Balan's research [15] explored the way in which the topics of the Instagram posts of a major sports equipment brand influenced the recognition received by its publications.…”
Section: Social Network Services In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the use of social media in the business context, several works can be highlighted [15][16][17][18][19]. Balan's research [15] explored the way in which the topics of the Instagram posts of a major sports equipment brand influenced the recognition received by its publications.…”
Section: Social Network Services In Organizationsmentioning
confidence: 99%
“…Giakoumaki and Krepapa [19] analyzed how the contents of luxury brands on the Instagram platform can obtain greater or lesser recognition, depending on whether the publication came from one source or another. The authors found that the recognition when the source of the publication was a personal account was greater than when the content was published by an influencer or by the corporate account of the company.…”
Section: Social Network Services In Organizationsmentioning
confidence: 99%
“…With the advancement of the digital 21st century, the ontological concept of community acceptance and influence remains similar to what it was decades ago. As a global communication medium, social media hosts networks of users; social media makes real‐time interactions easier (Alves et al, 2016; Felix et al, 2017; Giakoumaki & Krepapa, 2019; Mas‐Tur et al, 2016) and encourages brands to enhance their interaction with consumers (Malthouse et al, 2013) by engaging in brand‐related activities in online communities (Ibrahim et al, 2017). Online brand communities (OBCs) have evolved to allow larger numbers of individuals to interact with other users to form a collective virtual environment that is influenced by the members within the community.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have typically argued that functional motivation emerges from the behavioral type of loyalty toward brands, which is commonly based on the actual purchasing behavior of customers (Dick & Basu, 1994; Eggert et al, 2019; Gorlier & Michel, 2020; Jacoby & Kyner, 1973; Ozuem et al, 2016). In contrast, a brand that is central to a customer's value system and has symbolic significance to them causes them to remain with the brand (Aaker, 1997; Giakoumaki & Krepapa, 2020; Heitmann et al, 2020; Jacob et al, 2020). Several authors have investigated the sole influence of brand symbolism on motivating customers to integrate the brand as part of their social identity and reinforce their view of self (Swaminathan et al, 2020), ultimately leading to customers engaging with the brand or other consumers through social media (Giakoumaki & Krepapa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a brand that is central to a customer's value system and has symbolic significance to them causes them to remain with the brand (Aaker, 1997; Giakoumaki & Krepapa, 2020; Heitmann et al, 2020; Jacob et al, 2020). Several authors have investigated the sole influence of brand symbolism on motivating customers to integrate the brand as part of their social identity and reinforce their view of self (Swaminathan et al, 2020), ultimately leading to customers engaging with the brand or other consumers through social media (Giakoumaki & Krepapa, 2020). There is a consistent body of evidence, however, suggesting that information completeness and a need for bridging social capital are predictors of customer satisfaction and relationship commitment to brand communities (Cheng et al, 2018; Gorlier & Michel, 2020).…”
Section: Introductionmentioning
confidence: 99%